Obesity Modifies the Proteomic Profile of the Periodontal Ligament - Nogueira, Andressa V. B. [UNESP]; Lopes, Maria Eduarda S. [UNESP]; Marcantonio, Camila C. [UNESP]; Salmon, Cristiane R.; Mofatto, Luciana S.; Deschner, James; Nociti-Junior, Francisco H.; Cirelli, Joni A. [UNESP] (MDPI, 2023)
This study aimed to assess the obesity effects on the proteomic profile of the periodontal ligament of rats submitted to obesity induction by a high-fat diet. Eight Holtzman rats were divided into control (n = 3) and obese (n = 5) groups. The maxillae were histologically processed for laser capture microdissection of the periodontal ligament of the first maxillary molars. Peptide mixtures were analyzed by LC-MS/MS. A total of 1379 proteins were identified in all groups. Among them, 335 (24.30%) were exclusively detected in the obese group, while 129 (9.35%) proteins were uniquely found in the control group. Out of the 110 (7.98%) differentially abundant proteins, 10 were more abundant and 100 had decreased abundance in the obese group. A gene ontology analysis showed some proteins related to obesity in the “extracellular exosome” term among differentially identified proteins in the gene ontology cellular component terms Prelp, Sec13, and Sod2. These three proteins were upregulated in the obese group (p < 0.05), as shown by proteomic and immunohistochemistry analyses. In summary, our study presents novel evidence that the proteomic profile of the periodontal ligament is altered in experimental obesity induction, providing a list of differentially abundant proteins associated with obesity, which indicates that the periodontal ligament is responsive to obesity.
Keywords: obesity; periodontal ligament; prolargin; protein Sec13 homolog; proteomics; superoxide dismutase